JWST/NIRCam Narrowband Survey of Paβ Emitters in the Spiderweb Protocluster at z = 2.16 - Rhythm Shimakawa; J. M. Pérez-Martínez; Helmut Dannerbauer; Yusei Koyama; Tadayuki Kodama; Pablo G. Pérez-González; Chiara D’Eugenio; Yuheng Zhang; Abdurrahman Naufal; Kazuki Daikuhara (The Astrophysical Journal, 2024)
We report the initial result of our Pa β narrowband imaging on a protocluster with the JWST Near Infrared Camera (NIRCam). As NIRCam enables deep narrowband imaging of rest-frame near-infrared lines at z > 1, we target one of the most studied protoclusters, the Spiderweb protocluster at z = 2.16, in which previous studies have confirmed more than a hundred member galaxies. The NIRCam F405N narrowband filter covers in the Pa β line the protocluster redshift given by known protocluster members, allowing for the search for new member candidates. The weight-corrected color–magnitude diagram obtained 57 sources showing narrowband excesses, 41 of which satisfy further color selection criteria for limiting the sample to Pa β emitter candidates at z ∼ 2.16, and 24 of them do not have H α emitter counterparts. The Pa β emitter candidates appear to follow the spatial distribution of known protocluster members; however, follow-up spectroscopic confirmation is required. Only 17 out of 58 known H α -emitting cluster members are selected as Pa β emitters in the current data, albeit the rest fall out of the narrowband selection owing to their small Pa β equivalent widths. We derive the Pa β luminosity function in the Spiderweb protocluster, showing a normalization density of $log{φ }^{* }=-2.53± 0.15$ at a characteristic Pa β luminosity of $logL^{* }=42.33± 0.17$ . Furthermore, we examine the possibility of detecting faint line emitters visible only in the narrowband image but find no promising candidates.